Peran Perguruan Tinggi Dalam Menumbuhkan Budaya Anti Korupsi Di Indonesia - Saifulloh, Putra Perdana Ahmad (Jurnal Hukum & Pembangunan, 2017)
Post – reform, anti – corruption agenda into a central theme of law enforcement in Indonesia. Corruption is crime that has personality and characteristic as an extraordinary crime. To eradicate corruption, Parliament and Government have made regulation of legislation and formed corruption eradication institution. The institution that is still trusted by public for doing corruption eradication is Corruption Eradication Commission (KPK). KPK formed because the corruption eradication is done by police and prosecutor have not optimal. The effort which has been done by KPK, Prosecutor and Police is action effort that requires a big budget. Corruption eradication will never succeed and optimal in case country just depends on law enforcement institution. Actually the lowest cost of corruption eradication effort is prevention. This college has a central role in corruption prevention thing, especially in growing anti - corruption culture, increasing awareness of law and internalizing integrity values toward college student. The college student are candidate of nation leader in the future who need to protected in order to get off from corruption behavior or corruption crime. Therefore maximize of Tri Dharma in college increasing effort anti - corruption culture for college student and society.